2016
DOI: 10.18632/oncotarget.7614
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin (TSLP) inhibits human colon tumor growth by promoting apoptosis of tumor cells

Abstract: Thymic stromal lymphopoietin (TSLP) has recently been suggested in several epithelial cancers, either pro-tumor or anti-tumor. However, the role of TSLP in colon cancer remains unknown. We here found significantly decreased TSLP levels in tumor tissues compared with tumor-surrounding tissues of patients with colon cancer and TSLP levels negatively correlated with the clinical staging score of colon cancer. TSLPR, the receptor of TSLP, was expressed in all three colon cancer cell lines investigated and colon tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…How TSLPR and IL-7Rα expression is regulated during this process remains unknown. A similar finding was reported in colon cancer, where the tumor, but not normal tissues expressed functional TSLPR 13 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…How TSLPR and IL-7Rα expression is regulated during this process remains unknown. A similar finding was reported in colon cancer, where the tumor, but not normal tissues expressed functional TSLPR 13 .…”
Section: Discussionsupporting
confidence: 85%
“…The possible source of TSLP in these tumor microenvironments was not fully investigated, and the identity of critical TSLP-responding cells was also not clear. Although TSLP has been suggested to play a role in promoting some human cancers mentioned above, several studies have pointed to an anti-tumor role of TSLP in skin, colon, and early stage breast cancers in murine models, emphasizing the need to understand the impacts of TSLP on various cell types in tumor microenvironments 1013 . The TSLP receptor (TSLPR), composed of TSLPR chain and the interleukin 7 receptor α chain (IL-7Rα), is widely expressed on various immune cells, including B cells, mast cells, macrophages, dendritic cells (DCs), basophils, CD4 + , CD8 + , and regulatory T cells 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymic stromal lymphopoietin has been shown to block early breast carcinogenesis through the induction of Th2 cells . Thymic stromal lymphopoietin can inhibit colon cancer by inducing apoptosis of cancer cells . Thymic stromal lymphopoietin and Th2 cells also mediate resistance to carcinogenesis in mice with epidermal barrier defect .…”
Section: Effector Cells In Allergy and Cancermentioning
confidence: 99%
“…But, in the middle and the late stage, the level of the TSLP expression was correlated with tumor growth and metastasis [12], and tumor-derived TSLP could act on TSLPR + endothelial cells to promote angiogenesis in cervical cancer [41]. Conversely, Di Piazza and Demehri demonstrated that TSLP exerted a tumor-suppressing role in the murine model of skin cancer [26,40] through the engagement of TSLPR [42]. e present study shows for the first time that the expressions of TSLP, TSLPR, and OX40L, which were the key target proteins of the TSLP-OX40L pathway, were increased in the tumor microenvironment of mice bearing with HCC.…”
Section: Downregulatedmentioning
confidence: 99%